2005
DOI: 10.1177/10634266050130030601
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Strength Assessment Scores for Youth With and Without ED Across the Youth and Parent Rating Scales of the BERS-2

Abstract: Edition (BERS-2;Epstein, 2004). The BERS-2 is a standardized rating scale system that assesses the emotional and behavioral strengths of children and youth. Separate studies compared the perceptions of youth and parents of youth with emotional disturbance (ED) to youth and parents of youth without ED. Participants in Study 1 included 71 children verified with ED according to state special education guidelines and 386 children without ED.Participants in Study 2 included 82 parents of children with ED and 411 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
1
9
3
Order By: Relevance
“…The BERS-2 has a factor structure that assesses the dimensions of Interpersonal Strength, Family Involvement, Intrapersonal Strength, School Functioning, and Affective Strength. The factor structure has been replicated across several samples and has been found to be a valid and reliable measure (Benner et al 2008;Buckley et al 2006;Uhing et al 2005). Of particular importance to the current study, the cross informant agreement of the BERS-2 has been found to be acceptable.…”
Section: Introductionmentioning
confidence: 79%
“…The BERS-2 has a factor structure that assesses the dimensions of Interpersonal Strength, Family Involvement, Intrapersonal Strength, School Functioning, and Affective Strength. The factor structure has been replicated across several samples and has been found to be a valid and reliable measure (Benner et al 2008;Buckley et al 2006;Uhing et al 2005). Of particular importance to the current study, the cross informant agreement of the BERS-2 has been found to be acceptable.…”
Section: Introductionmentioning
confidence: 79%
“…Efforts to establish validity for specific purposes or populations should be ongoing (Merrell et al 2003). Such efforts are particularly warranted in the assessment of students with ED, given confusion with vague definitions and the comprehensive nature of the evaluation process (Uhing et al 2005). The purpose of this study was to extend validation efforts for the teacher scale of the BERS-2.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted populations include students identified as having ED and served in public school settings. Efforts to demonstrate the uses of behavior rating scales for students with ED are necessary in order to: (a) counteract the problems resulting from vague definitions in the education and mental health fields, and (b) contribute to comprehensive, multifaceted assessments (Uhing et al 2005).…”
mentioning
confidence: 99%
“…ACBQ was created in 1979 for assessing mental disorders and children's adaptation with their environment (30). This test contains 113 questions with 0-2 score.…”
Section: Methodsmentioning
confidence: 99%